Lactobacillus plantarum Y44 alleviates oxidative stress by regulating gut microbiota and colonic barrier function in Balb/C mice with subcutaneous d-galactose injection. Issue 1 (16th December 2020) - Gao, Yuan; Liu, Yujun; Ma, Fenglian; Sun, Mengying; Song, Yinglong; Xu, Dongxue; Mu, Guangqing; Tuo, Yanfeng
Abstract : The effect of L. plantarum Y44 administration on oxidative stress in Balb/C mice included the recovery of the gut microbiota and intestinal barrier function, influencing the glycerophospholipid metabolism, and activating Nrf-2/Keap-1 pathway. Abstract : Probiotics have been proved to ameliorate the symptoms of the host induced by oxidative stress. In this study, the protective effects of Lactobacillus plantarum Y44 on Balb/C mice injured by d -galactose (d -gal)-injection were examined. Six weeks of continuous subcutaneous d -gal injection caused liver and colon injury of the Balb/C mice. L. plantarum Y44 administration significantly reversed the injury by modulating hepatic protein expressions related to the Nrf-2/Keap-1 pathway, and enhancing expressions of colonic tight junction proteins. L. plantarum Y44 administration restored the d -gal injection-induced gut microbiota imbalance by manipulating the ratio of Firmicutes / Bacteroidetes (F/B) and Proteobacteria relative abundance at the phylum level, and manipulating relative abundances of Lactobacillaceae, Muribaculaceae, Ruminococcaceae, Desulfovibrionaceae, and Prevotellaceae at the family level. Moreover, the d -gal injection-induced glycerophospholipid metabolism disorder was ameliorated, evidenced by the decline of phosphatidyl ethanolamine (PE), phosphatidylcholine (PC), phosphatidyl serine (PS), and lysophosphatidyl choline (LysoPC) levels in the serum of the mice after the L. plantarum Y44 administration. Spearman correlation analysis revealed a significant correlation between changes in gut microbiota composition, glycerophospholipid levels, and oxidative stress-related indicators. In summary, L. plantarum Y44 administration ameliorated d -gal injection-induced oxidative stress in Balb/C mice by manipulating gut microbiota and intestinal barrier function, and further influenced the glycerophospholipid metabolism and hepatic Nrf-2/Keap-1 pathway-related protein expressions.